2015
DOI: 10.1016/j.dib.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiles of valvular interstitial cells cultured on tissue culture polystyrene, on 2D hydrogels, or within 3D hydrogels

Abstract: Valvular interstitial cells (VICs) actively maintain and repair heart valve tissue; however, persistent activation of VICs to a myofibroblast phenotype can lead to aortic stenosis (Chen and Simmons, 2011) [1]. To better understand and quantify how microenvironmental cues influence VIC phenotype, we compared expression profiles of VICs cultured on/in poly(ethylene glycol) (PEG) gels to those cultured on tissue culture polystyrene (TCPS), as well as fresh isolates. Here, we present both the raw and processed mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…mRNA expression levels in VICs cultured on TCPS, 2D hydrogels, or within 3D hydrogels were compared to freshly isolated VICs using a porcine DNA microarray [23]. VICs cultured on TCPS had differential expression compared to freshly isolated cells for 3304 probesets (out of 25470), where a difference was defined as a fold change greater than 2 or less than −2 and a p-value less than 0.05 to achieve statistical and biological significance (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…mRNA expression levels in VICs cultured on TCPS, 2D hydrogels, or within 3D hydrogels were compared to freshly isolated VICs using a porcine DNA microarray [23]. VICs cultured on TCPS had differential expression compared to freshly isolated cells for 3304 probesets (out of 25470), where a difference was defined as a fold change greater than 2 or less than −2 and a p-value less than 0.05 to achieve statistical and biological significance (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…By now, various in vitro CAVD models have been described in the literature [3][4][5][6][7]. Beside conventional 2D cell culture, 3D models have recently become increasingly popular [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…By now, various in vitro CAVD models have been described in the literature [3][4][5][6][7]. Beside conventional 2D cell culture, 3D models have recently become increasingly popular [6][7][8][9][10]. These 3D models are more likely to rebuild the actual cell and ECM interactions of the native valve [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype of valvular interstitial cells (VICs), the most abundant and plastic cell population in the valve, can be modulated by the properties of cell culture substrate/matrix . It has been revealed that matrix stiffness affects the activation and osteogenic differentiation of VICs . Moreover, the morphology and architecture of valvular ECM have been shown to instruct the attachment and spreading of VICs .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It has been revealed that matrix stiffness affects the activation and osteogenic differentiation of VICs. [8][9][10] Moreover, the morphology and architecture of valvular ECM have been shown to instruct the attachment and spreading of VICs. 11,12 Several studies have performed uniaxial tensile testing on tissue-engineered scaffolds, 13,14 but uniaxial testing is insufficient to fully characterize the scaffold mechanical properties as it fails to capture the complex cross-coupling (stress along one axis is affected by the strain level along the perpendicular axis) experienced by the anisotropic tissues.…”
mentioning
confidence: 99%